The anthropology of citizenship : a reader - Lazar, Sian. (Chichester, West Sussex : Wiley-Blackwell, 2013)
'The Anthropology of Citizenship introduces the theoretical foundations of and cutting edge approaches to citizenship in the contemporary world, in local, national and global contexts. Key readings provide a cross-cultural perspective on citizenship practices, and an individual citizen's relationship with the state. Introduces a range of exciting and cutting edge approaches to citizenship in the contemporary world Provides key readings for students and researchers who wish to gain an understanding of citizenship practices, and an individual's relationship with the state in a global context Offers an anthropological perspective on citizenship, the self and political agency, with a focus on encounters between citizens and the state in education, law, development, and immigration policy Provides students with an understanding of the theoretical foundations of citizenship, as characterized by liberal and civic republican ideas of political belonging and exclusion Explores how citizenship is constructed at different scales and in different spaces Twenty-five key writings identify what is a new and vibrant subfield within politics and anthropological research'--
'Introduces a range of exciting and cutting edge approaches to citizenship in the contemporary world'--
Includes biblioigraphical references and index.
Keywords: Citizenship -- Cross-cultural studies; Civil society -- Cross-cultural studies